Low‐grade and high‐grade mammary carcinomas in WAP‐T transgenic mice are independent entities distinguished by Met expression. Issue 6 (26th September 2012) - Otto, Benjamin; Gruner, Katharina; Heinlein, Christina; Wegwitz, Florian; Nollau, Peter; Ylstra, Bauke; Pantel, Klaus; Schumacher, Udo; Baumbusch, Lars O.; Martin‐Subero, José Ignacio; Siebert, Reiner; Wagener, Christoph; et al.
Abstract Mammary carcinomas developing in SV40 transgenic WAP‐T mice arise in two distinct histological phenotypes: as differentiated low‐grade and undifferentiated high‐grade tumors. We integrated different types of information such as histological grading, analysis of aCGH‐based gene copy number and gene expression profiling to provide a comprehensive molecular description of mammary tumors in WAP‐T mice. Applying a novel procedure for the correlation of gene copy number with gene expression on a global scale, we observed in tumor samples a global coherence between genotype and transcription. This coherence can be interpreted as a matched transcriptional regulation inherited from the cells of tumor origin and determined by the activity of cancer driver genes. Despite common recurrent genomic aberrations, e.g. gain of chr. 15 in most WAP‐T tumors, loss of chr. 19 frequently occurs only in low‐grade tumors. These tumors show features of "basal‐like" epithelial differentiation, particularly expression of keratin 14. The high‐grade tumors are clearly separated from the low‐grade tumors by strong expression of the Met gene and by coexpression of epithelial (e.g. keratin 18) and mesenchymal (e.g. vimentin) markers. In high‐grade tumors, the expression of the nonmutated Met protein is associated with Met‐locus amplification and Met activity. The role of Met as a cancer driver gene is supported by the contribution of active Met signaling to motility and growth of mammary tumor‐derived cells. Finally, we discuss the independent origin of low‐ and high‐grade tumors from distinct cells of tumor origin, possibly luminal progenitors, distinguished by Met gene expression and Met signaling.